A PETROLOGIC AND ISOTOPIC STUDY OF LODRANITES: EVIDENCE FOR EARLY FORMATION AS PARTIAL MELT RESIDUES FROM HETEROGENEOUS PRECURSORS - McCoy T.J.; Keil K.; Clayton R.N.; Mayeda T.K.; Bogard D.D.; Garrison D.H.; Wieler R. (My University, 1997)
We have conducted petrologic, chemical, and isotopic studies of lodranites in an attempt to constrain their genesis. Lodran, Gibson, Y-791491, Y-791493, Y-74357, Y-8002, Y-75274, MAC 88177, LEW 88280, EET 84302, FRO 90011, and QUE 93148 are classified as lodranites. Lodranites and acapulcoites are indistinguishable on the basis of oxygen isotopic compositions but are distinct in average grain sizes of their mafic silicates, with lodranites being significantly coarser-grained. Lodranites exhibit a diverse range of petrologic and mineralogic features: they range widely in mafic silicate compositions (Fa3-13), plagioclase (0-11.4 vol%), Fe,Ni metal (0.5-20 vol%), and troilite (0.2-5.3 vol%) contents; and shock levels (S1-S4). They appear to have experienced high peak temperatures and rapid cooling in the temperature range recorded by metallographic cooling rates (i.e., 700-350°C). The only dated lodranite, Gibson, cooled to Ar closure temperatures at 4.49 +/- 0.01 Ga.Lodranites formed from chemically and isotopically heterogeneous precursors in which the mineral and oxygen isotopic compositions were correlated. Heating of their parent body to temperatures between ~1050-1200°C resulted in formation of Fe,Ni-FeS and basaltic partial melts. Depletions of troilite and/or plagioclase in most lodranites testify to the removal of some of these partial melts, although melt migration was complex. Lodranites appear to have experienced a complex cooling history of slow cooling at high temperatures, followed by rapid cooling at intermediate temperatures, possibly related to breakup of the parent body. Lodranites were liberated from their parent body during 1-3 impact events, with most having cosmic ray exposure ages of 5.5-7 Ma. The acapulcoites are samples from the same parent body but were heated to lower temperatures and, thus, experienced lower degrees of partial melting.